Depressed patients in remission show an interaction between variance in the mineralocorticoid receptor NR3C2 gene and childhood trauma on negative memory bias. (June 2015) - Vrijsen, Janna N.; Vogel, Susanne; Arias-Vásquez, Alejandro; Franke, Barbara; Fernández, Guillén; Becker, Eni S.; Speckens, Anne; van Oostrom, Iris
Abstract : Background: Genetic, environmental, and cognitive factors play a role in the development and recurrence of depression. More specifically, cognitive biases have been associated with depression risk genes and life events. Recently, the mineralocorticoid receptor NR3C2 gene, and in particular the rs5534 polymorphism, has been associated with negative memory bias, at least in healthy individuals who experienced severe life adversity. The current study examined the interaction between the rs5534 genotype and different types of adverse life events in a sample of depressed patients in remission. Materials and methods: A total of 298 depressed patients in remission performed an incidental emotional memory task (negative and positive words). Life adversity, childhood trauma, and recent adversity were measured using a self-report questionnaire. NR3C2 rs5534 by life adversity, as well as childhood trauma and recent adversity interactions were analyzed for negative and positive memory bias using analyses of covariance. Results: The significant interaction between rs5534 and childhood trauma on negative memory bias ( P =0.046) indicated that risk 'A' allele carriers with childhood trauma tended to show more negative memory bias compared to individuals homozygous for the G allele who had experienced childhood trauma and A allele carriers without childhood trauma. No interaction effects with life adversity or recent adversity were found. Also, no main effect of rs5534 on memory bias was found, although we had insufficient power for this analysis. Conclusion: An association of the NR3C2 gene and childhood trauma with negative memory bias was found in depressed patients in remission, which extends previous findings in a healthy population.